2023
DOI: 10.1007/s10854-023-10270-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CuO doping on structural features, optical absorption and photoluminescence behavior of ZnO-based glasses

Abstract: Glasses composed of ZnO–SiO2–B2O3–In2O3 with the addition of different content of CuO were prepared by a popular melt–quenching methodology. The effect of the addition of copper oxide in the glass network was investigated using density, FTIR spectroscopy, optical absorption, and photoluminescence spectroscopy. By increasing the concentration of CuO, a decrease in the density is observed, indicating structural changes in the glass network. The structural building units of glasses are $${\mathrm{BO}}_{3}$$ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Therefore, the PL spectra indicate the existence of both Cu + and Cu 2+ ions, contributing to the observed emission peaks. It was also observed that with the increase in CuO concentration, the PL intensity decreased; this is attributed to the loss of excited energy from copper ions to the host lattice [51]. The decrease in the PL intensity with higher concentration made the PL signal of the Cu8 sample indistinguishable from the noise.…”
Section: Structural and Physicochemical Characterizationmentioning
confidence: 94%
See 4 more Smart Citations
“…Therefore, the PL spectra indicate the existence of both Cu + and Cu 2+ ions, contributing to the observed emission peaks. It was also observed that with the increase in CuO concentration, the PL intensity decreased; this is attributed to the loss of excited energy from copper ions to the host lattice [51]. The decrease in the PL intensity with higher concentration made the PL signal of the Cu8 sample indistinguishable from the noise.…”
Section: Structural and Physicochemical Characterizationmentioning
confidence: 94%
“…The luminescence peak at 475 nm is associated with the 3d 9 4s 1 -4s 2 3d 10 transition of Cu 2+ ions [51,53]. The shoulder peak at 523 nm is a consequence of the transition from the degraded T 1g and T 2g levels to the 1 A g energy level of the Cu + copper ions [51,54]. This transition arises from the interaction between NBOs with the Cu 2+ .…”
Section: Structural and Physicochemical Characterizationmentioning
confidence: 95%
See 3 more Smart Citations